The Effect of Oleuropein on the Treatment of Allergic Rhinitis - Cil, Özge Çaglar; Büyük, Basak; Eroglu, Hüseyin Avni; Sehitoglu, Hilal (International Archives of Otorhinolaryngology, 2025)
Allergic rhinitis is a disease that negatively affects social and work life and sometimes does not respond to many treatments. Therefore, new treatments are needed. For the prevention and treatment of allergies, oleuropein has been emphasized, and positive results have been shown in the literature.To investigate the effects of general and topical oleuropein during the allergic rhinitis period and the histopathological changes in the nasal mucosa compared with steroid nasal sprays and control group in rats.We developed an experimental animal model with 44 rats divided into 6 groups. Except for the control group, the allergic rhinitis in the other five groups was created with ovalbumin. As treatment, saline was administered to group 3, steroids, to group 4, oleuropein, to group 5, and steroids and oleuropein were administered to group 6. The effects of the drugs were examined histopathologically and the levels of immunoglobulin E (IgE) in the blood were compared.Considering the symptomatic findings in rats, we could observe that allergic rhinitis occurred. Based on the IgE levels and histopathological findings, we have statistically shown that oleuropein may be effective in treatment of allergy rhinitis.Oleuropein has been shown to be useful in the treatment of allergic rhinitis in an animal model, but further studies are needed before it is introduced into the medical practice.
Keywords: allergic rhinitis; oleuropein; steroid; treatment; ovalbumin